THE CONCEPT OF PEACE IN THE THEORY OF INTERNATIONAL RELATIONS (Годишен зборник на Филозофски факултет - Скопје, 2023)
The development of the peace concept is closely related to the development of the concept of the state and hence to the efforts for elimination of war as an instrument for resolving disputes between states. In that context, war and peace are traditionally treated as mutually exclusive concepts, i.e., war implies violence, while peace, nonviolence. So, the end of war marks the beginning of peace and vice versa. Therefore, both concepts simultaneously represent the inevitable outcomes of the continuous and dynamic nature of social interaction in the international system, foreshadowing future war for nations and states that are currently at peace and, on the other hand, foreshadowing peace for nations and states that are currently at war. Starting from the indicated traditional understanding of the concepts of peace and war, as well as from the fact that the establishment of peace research begins during the 80s of the XX century, the focus in the paper is specifically placed on the analysis of the peace concept through the prism of the theory of international relationships. Namely, it is indisputable that until the establishment of peace and security research and studies, issues of peace and security are generally considered and interpreted within the framework of the various theoretical approaches for international relations. Hence, the paper more specifically explores the evolutionary character of the perceptions and understanding of the peace concept, especially from the perspective of: federalism, neorealism, liberalism and functionalism. The main goal is to give an answer to the question - What is peace and how can it be achieved, according to the indicated theoretical approaches?